Managing Entry or Expansion: Is Vietnam a Feasible Market for Advanced Food Processing Solution Providers? - Trung QUANG DINH; Hilmar Þór HILMARSSON (Revista de Management Comparat International)
Vietnam is large food producer and exporter. Currently the country is a low middle income economy, but is striving to increase value added of its products and export more to high income countries. During this transition Vietnam can be a feasible market for producers of advanced processing solutions. This article analysis and assesses the seafood and livestock market in Vietnam. The conclusion is that there is an opportunity for advanced processing solution providers to sell processing solutions in both fisheries and livestock sectors. In the short run growth potential for these providers seem to be in fisheries sector while the medium or long term potential seems to be in the livestock sector.